A Multifunctional Photonic Integrated Circuit for Diverse Microwave Signal Generation, Transmission, and Processing. Issue 6 (10th May 2019) - Zou, Xihua; Zou, Fang; Cao, Zizheng; Lu, Bing; Yan, Xianglei; Yu, Ge; Deng, Xiong; Luo, Bin; Yan, Lianshan; Pan, Wei; Yao, Jianping; Koonen, Antonius M. J.
Abstract: Microwave photonics (MWP) studies the interaction between microwaves and optical waves for the generation, transmission, and processing of microwave signals (i.e., three key domains), taking advantage of the broad bandwidth and low loss offered by modern photonics. Integrated MWP using photonic integrated circuits (PICs) can reach a compact, reliable, and green implementation. Most PICs, however, are recently developed to perform one or more functions restricted inside a single domain. Herein, as highly desired, a multifunctional PIC is proposed to cover the three key domains. The PIC is fabricated on an InP platform by monolithically integrating four laser diodes and two modulators. Using the multifunctional PIC, seven fundamental functions across microwave signal generation, transmission, and processing are demonstrated experimentally. Outdoor field trials for electromagnetic environment surveillance along in‐service high‐speed railways are also performed. The success of such a PIC marks a key step forward for practical and massive MWP implementations. Abstract : A monolithically integrated photonic circuit is developed for the generic purpose of microwave photonics, providing seven fundamental functions across microwave signal generation, transmission, and processing. The multifunctional circuit is directly deployed for real‐world applications, including high‐speed railways and broadband wireless communications. This work transfers integrated microwave photonics from the laboratory to daily life, and toward a wide range of applications.